Ethnocultural Empathy Level: A Study Case in Counseling Students - Heriyani, Eka; Yuwono , Bambang Budi; Lasan, Blasius Boli; Hitipeuw , Immanuel (Kuras Institute, 2024)
Ethnocultural empathy is essential for a counselor to understand the client's condition. Mutual respect and realizing the difference are essential for relating to others in a multicultural environment. However, in the present, empathy cannot be obtained easily but should be devised. This research examines the level of ethnocultural emphasis on the teacher's students' Guidance and counseling. This study is descriptive quantitative research, data collecting using the instrument The Scale of Ethnocultural Empathy with 31 questions. Instrument validity refers to the Corrected Item score-Total Correlation >= 0.300 with a Cronbach's Alpha score 721. The sample involved prospective students of guidance and counseling teachers, with as many as 213 respondents. Descriptive statistics are used to interpret and explain the numerical data presented. In addition, to encourage respondents to participate in this research, an online instrument was created with a time-based fee structure, which made the implementation process more efficient. With an analysis of ethnocultural empathy levels in prospective school counselors based on gender and ethnicity, this study identified that prospective school counselors have ethnocultural empathy levels based on gender and ethnicity that exist in four dimensions, namely at the average level. Therefore, the university must be able to pay special attention to the cultivation of ethnocultural empathy for prospective teacher guidance and counseling students.